Hubungan Pengetahuan, Konsumsi Tablet FE Dan Status Gizi Dalam Penanganan Anemia Pada Remaja Putri Di Desa Nania Kota Ambon Tahun 2022 : Correlation between Knowledge, FE Tablet Consumption and Nutritional Status in Handling Anemia in Young Girls in Nania Village, Ambon City in 2022 - Soekardy, Anastasya (Indonesian Scholar Journal of Nursing and Midwifery Science, 2023)
Introduction: Anemia is a condition where the level of hemoglobin (Hb) in the blood is lower than the normal number. According to the World Health Organization (WHO) In 2020 the prevalence of Anemia in adolescents in the world ranges from 40-80%, while in Indonesia itself it is 39,1%, Based on data from all these age groups, women have the highest prevalence of Anemia, including young women. The target for handling Anemia in Maluku province is 30%, and the achievement of handlers is 35%. This shows that the achievement of Anemia treatment has not been maximized and still requires further treatment. Anemia in adolescents has the impact of decreased concentration when carrying out learning activities, and decreased physical fitness can cause growth disorders so that height and weight do not reach normally. Prevention and prevention of Anemia in adolescents can be done by increasing knowledge about the pattern of food intake of iron sources, and routine consumption of iron supplementation by consuming blood-added tablets (FE), therefore, adolescents are expected to be able to apply Anemia prevention measures in daily life. Method: This research is descriptive-analytic by using a cross-sectional approach. The population of this study is young women in Nania Village, Ambon City in 2022. The sample is 63 people. With the Total Population Sampling method. The analysis uses the Chi-Square Test. Results: The results of statistical tests show that there is no relationship between knowledge and Anemia treatment (p-value 0,487) and Nutritional status (p-value of 1,000). There is a relationship between FE Tablet Consumption and Handling of Anemia (p-value 0,003). With an OR value of 0,727; a min value of 0,164; and a max of 3,22. Discussion: there is a significant relationship between the consumption of FE tablets in treating Anemia in adolescent girls with an OR value of 0,727 and affecting a minimum of 0,164% and a maximum of 3,22%. which means the strength of the variable relationship in the strong category. Suggestions are expected for further researchers to examine other variables related to the symptoms of this Anemia treatment.